Safety and efficacy of biliary stenting combined with iodine-125 seed strand followed by hepatic artery infusion chemotherapy plus lenvatinib with PD-1 inhibitor for the treatment of extrahepatic cholangiocarcinoma with malignant obstructive jaundice - Lin, Long-Wang; Ke, Kun; Chen, Rong; Yang, Wei-Zhu; Huang, Ning; Wu, Zheng-Zhong (Frontiers in Immunology, 2024)
Objectives: To evaluate the efficacy and safety of biliary stenting implantation with iodine-125 seed strand (SI) followed by hepatic artery infusion chemotherapy (HAIC) plus lenvatinib (Len) with programmed cell death-1 (PD-1) inhibitor for patients diagnosed with extrahepatic cholangiocarcinoma (ECC) and malignant obstructive jaundice (MOJ).In this single-center retrospective study, the data of ECC patients with MOJ from March 2015 to January 2023 were assessed. Using probability score matching (PSM), the selection bias of patients was reduced. Primary study outcomes included overall survival (OS) and progression-free survival (PFS), OS, and PFS were performed using the Kaplan-Meier method and evaluated with the log-rank test.Results: A total of 104 patients were enrolled finally, including 52 patients treated with interventional therapy (SI+HAIC) plus Len with PD-1 inhibitor (SI+HAIC+Len+P group) and 52 patients treated with interventional therapy (SI+HAIC) plus lenvatinib (SI+HAIC+Len group). 26 pairs of patients were matched after PSM analysis. After PSM analysis, the median OS and PFS in SI+HAIC+Len+P group were significantly longer compared to those in SI+HAIC+Len group (OS:16.6 vs. 12.3 months, P = 0.001; PFS:12.6 vs 8.5 months, P = 0.004). The DCR was significantly different between groups (P = 0.039), while ORR not (P = 0.548). The addition of PD-1 inhibitors was generally well tolerated without treatmentassociated mortality.Interventional therapy (SI+HAIC) plus Len with PD-1 inhibitor was effective for ECC patients accompanied by MOJ with a manageable safety profile.